High-rigidity impact-resistant foam masterbatch, adhesive tape and preparation method of high-rigidity impact-resistant foam masterbatch

By using high-stiff impact-resistant foam masterbatch composed of block copolymers and acrylate monomers in large-screen display equipment, the shortcomings of existing foam tapes in terms of impact resistance and stiffness are solved, and higher impact resistance and stiffness are achieved, and the stability and life of the equipment are enhanced.

CN119799222AActive Publication Date: 2025-04-11SUZHOU SHIHUA NEW MATERIAL TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202412000150.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing foam tape is difficult to take into account both impact resistance and stiffness in large-screen display equipment, resulting in cracks or falls off easily when falling or bent, affecting the stability and life of the equipment.

Method used

High-stiffness impact-resistant foam masterbatch composed of block copolymers, acrylate monomers, solvents and initiators are prepared by copolymerizing acrylate graft-modified block copolymers and acrylates in the same reaction vessel to form an interpenetrating network structure to improve the stiffness and impact resistance of the adhesive.

Benefits of technology

The stiffness of the foam tape is achieved above 13N/mm, and has excellent impact resistance, which can effectively prevent damage caused by bending or falling during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799222A_ABST
    Figure CN119799222A_ABST
Patent Text Reader

Abstract

The invention relates to a high-rigidity impact-resistant foam masterbatch, an adhesive tape and a preparation method of the high-rigidity impact-resistant foam masterbatch and the adhesive tape. The high-rigidity impact-resistant foam masterbatch comprises a block copolymer, an acrylate monomer, a solvent I and an initiator, when the mass part of the block copolymer is set as S and the mass part of the acrylate monomer is set as B, B / S is more than or equal to 1.5 and less than or equal to 5, and the theoretical TG after the acrylate monomer is independently copolymerized is-40 to-20 DEG C; the foam adhesive tape containing the foam master batch can be used as a buffer material for bonding large-size screen frames, the rigidity of the foam adhesive tape can be 13N / mm or above, and the foam adhesive tape has excellent impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of foam tapes, and in particular relates to a high-rigidity impact-resistant foam masterbatch, a tape and a preparation method thereof. Background Art

[0002] As the core component connecting the screen and the frame, foam tape ensures a solid connection between the two. With the popularization of large-screen display technology in modern display devices and smart products (such as smartphones, tablets, laptops and other consumer electronics), the importance of foam tape has become increasingly prominent. It not only needs to have excellent impact resistance to prevent the device from being damaged when it falls or collides; it also needs to have a certain degree of rigidity to cope with the bending of the screen and frame caused by the frequent opening and closing of these devices during use. In particular, large-screen flexible screens are subject to more significant stress and deformation during the bending process. If the foam tape is not rigid enough, it is easy to crack or even fall off during bending, causing the screen to loosen or damage. Therefore, the design of foam tape must take into account both impact resistance and rigidity to meet the high standards of modern smart devices for connection materials.

[0003] Current impact-resistant foam tape technology:

[0004] CN117730128A provides a pressure-sensitive adhesive having good impact resistance and high internal strength, comprising a) at least 50 wt % of at least one poly(meth)acrylate based on the total weight of the pressure-sensitive adhesive; b) 15-35 wt % of a synthetic rubber component based on the total weight of the pressure-sensitive adhesive, which includes at least one vinyl aromatic butadiene block copolymer and at least one vinyl aromatic isoprene block copolymer; and c) at least one tackifier resin compatible with the synthetic rubber component.

[0005] KR1020247026664 discloses an impact-resistant adhesive, which uses a toughening component with a core-shell structure to improve the impact resistance of a polyacrylate adhesive, especially in a side impact test.

[0006] However, none of the above patents mention how to achieve the rigidity requirement of the foam tape. In order to make the design of the foam tape take into account both impact resistance and rigidity, the present invention proposes a high-rigidity impact-resistant foam masterbatch, tape and preparation method thereof. The proposal of the present invention will promote the further development of large-screen display technology. Summary of the invention

[0007] In view of the current technical status, the purpose of the present invention is to provide a high-rigidity impact-resistant foam masterbatch, adhesive tape and a preparation method thereof. The foam adhesive tape can be used as a buffer material for bonding large-size screen frames, and can achieve a rigidity of more than 13N / mm and excellent impact resistance.

[0008] In order to solve the above technical problems, the first aspect of the present invention provides the following technical solutions:

[0009] A high-rigidity impact-resistant foam masterbatch, characterized in that it comprises a block copolymer, an acrylate monomer, a solvent, and an initiator; the mass fraction of the block copolymer is set to S, the mass fraction of the acrylate monomer is set to B, then 1.5≤B / S≤5, and the theoretical TG of the acrylate monomer after copolymerization alone is -40 to -20°C.

[0010] Preferably, the solid content of the high-rigidity impact-resistant foam masterbatch is 20-50%, the solvent is set to R parts by mass, and the initiator is set to Y parts by mass; then: 20%≤(S+B+Y) / (S+B+Y+R)≤50%.

[0011] Preferably, the block copolymer has a styrene content of >20%;

[0012] More preferably, the block copolymer has a star-shaped structure.

[0013] Preferably, the foam masterbatch is prepared by firstly carrying out acrylate grafting modification of the block copolymer and then carrying out acrylate copolymerization in the same reaction container.

[0014] Preferably, the block copolymer is one or more of SBS, SIS, and SEBS.

[0015] Preferably, the acrylic acid ester monomer is one or more of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, n-butyl acrylate, isobutyl acrylate, isooctyl acrylate, isobornyl acrylate, isobornyl methacrylate, cyclohexyl methacrylate, hydroxybutyl acrylate, urea-based acrylic acid prosthesis, ethyl diethylene glycol acrylate, and tert-butyl acrylate.

[0016] Preferably, the initiator is a peroxide and / or an azo compound; for example, benzoyl peroxide, tert-butyl peroxyhexahydroterephthalate, tert-butyl peroxypivalate, tert-butyl hydroperoxide, tert-butyl perbenzoate, azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, and further preferred initiators are azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO).

[0017] Preferably, the solubility parameter of the solvent 1 is 7.6-9.8, and the solvent 1 may be one or more of toluene, xylene, n-butyl acetate, methyl isobutyl ketone, isobutyl acetate, cyclohexane, t-tert-butyl acetate, and ethyl acetate.

[0018] In addition, other additives may be added to the high-rigidity impact-resistant foam masterbatch without affecting the desired effect of the present invention, such as chain transfer agents, antioxidants, flame retardants, etc.

[0019] Preferably, the chain transfer agent is one or more of isopropanol and dodecanethiol; the mass fraction of the chain transfer agent is set to L, 0.001‰≤L / S≤1‰.

[0020] The second aspect of the present invention provides a method for preparing a high-rigidity impact-resistant foam masterbatch, comprising the following steps:

[0021] N 2 In the atmosphere, add solvent 1 and all block copolymers into the reactor in sequence to make the solid content of the block copolymer 10-30%, and heat and reflux for 5-10 minutes;

[0022] 0.2B parts by mass of acrylic acid monomer and 0.0001 to 0.01S parts by mass of initiator are mixed uniformly. 2 After deoxygenation, add into the reactor and continue the reaction for 3-5h;

[0023] 0.8B parts by weight of acrylic acid monomer, 0.00008B to 0.008B parts by weight of initiator, and 0.8B parts by weight of solvent were mixed uniformly. 2 After deoxygenation, add dropwise to the reactor 1-1.5h and react for 1-2h;

[0024] Every 1 hour, add 0.00004B to 0.004B parts by mass of initiator until all the remaining initiator is added. After reacting for 1-2 hours, add the remaining solvent and cool to room temperature to obtain a high-rigidity impact-resistant foam masterbatch.

[0025] The third aspect of the present invention is to provide a method for preparing the high-rigidity impact-resistant foam tape, characterized in that it comprises, by mass, 100 parts of the above-mentioned foam masterbatch, 0.1-5 parts of a foaming agent, 0-300 parts of a tackifying resin, 0.1-5 parts of a curing agent, and 0-400 parts of a solvent II;

[0026] Except for solvent 2, the remaining components are calculated according to the solid components.

[0027] Preferably, the curing agent is one or more of an isocyanate curing agent, an epoxy curing agent, and a metal salt curing agent.

[0028] More preferably, the curing agent is a combination of an epoxy curing agent and a metal salt curing agent.

[0029] Preferably, the second solvent is one or more of toluene, ethyl acetate, heptane, butyl acetate, and butanone.

[0030] Preferably, the foaming agent is one or more of foaming microspheres, hydrocarbon foaming agents, and carbon dioxide foaming agents;

[0031] Preferably, the tackifying resin is one or more of terpene resins, rosin resins, esterified rosin resins, and petroleum resins.

[0032] A fourth aspect of the present invention provides a method for preparing a high-rigidity impact-resistant foam tape, comprising the following steps:

[0033] S1: Add materials into the container in the following order: Solvent 2 and tackifying resin are fully dissolved until no particles remain; then add foam masterbatch and stir at high speed for 10-30 minutes; add foaming agent and curing agent, mix well and adjust the solid content to 20-35% with solvent 2 to prepare coating solution;

[0034] S2: The coating liquid prepared above is filtered and degassed, and then evenly coated on a release film. After drying, foaming, and laminating, a high-rigidity impact-resistant foam tape is obtained.

[0035] Preferably, the coating liquid is filtered using a three-core 10um filter element.

[0036] Preferably, the drying process is: the coating liquid is evenly coated on the release film and continuously passed through a coating machine containing 7 ovens, continuously heated and dried to form a high-rigidity impact-resistant foam tape. Among them, the temperature of the first section is 60-70°C, the temperature of the second section is 70-85°C, the temperature of the third section is 85-110°C, the temperature of the fourth section is 110-155°C, the temperature of the fifth section is 110-155°C, the temperature of the sixth section is 130-110°C, and the temperature of the seventh section is 110-90°C.

[0037] The fifth aspect of the present invention provides an application of a high-rigidity impact-resistant foam tape, characterized in that the above-mentioned high-rigidity impact-resistant foam tape or the high-rigidity impact-resistant foam tape obtained by the above-mentioned preparation method is applied to modern display and smart devices.

[0038] The modern display and smart devices are devices that have display technology, smart functions, and can realize user interaction, such as: televisions, computers, tablets, learning machines, smart wearable devices, car displays, health testing equipment, smart watches, fitness trackers, smart glasses, smart home screens, AR devices, VR devices, smart robots, smart displays, somatosensory interaction devices, etc.

[0039] If not otherwise specified, the "room temperature" mentioned in the present invention is 23°C.

[0040] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0041] 1. In the same reaction vessel, the block copolymer is first modified by acrylate grafting, and then the foam masterbatch is prepared by acrylate copolymerization. The block copolymer molecular chain and the polyacrylate molecular chain are entangled with each other, which curbs stratification and is conducive to solvent coating. It avoids phase separation during the static standing of the coating liquid, which causes stratification of thicker foam tapes.

[0042] 2. Polyacrylate is micro-crosslinked through a curing agent to form an interpenetrating network structure with the block copolymer, increasing the stiffness and impact resistance of the adhesive.

[0043] 3. After the acrylate monomer is copolymerized alone, the theoretical TG is -40 to -20°C, which can ensure that the adhesion, impact resistance and stiffness of the foam tape meet the application requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Schematic diagram of stiffness test;

[0045] Figure 2 Schematic diagram of impact resistance test. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] In the following examples, the raw materials used are shown in Table 1:

[0048] Table 1 Composition of high stiffness impact resistant foam adhesive layer

[0049]

[0050]

[0051] Example 1

[0052] Preparation of Foam Masterbatch

[0053] According to the mass fraction, the composition of the foam masterbatch is as follows: the theoretical TG after the copolymerization of the acrylic ester monomer is -38.78°C;

[0054]

[0055] Prepare the foam masterbatch as follows:

[0056] 1. N 2In the atmosphere, 200 parts of toluene were placed in a 50L reactor, and 50 parts of SBS D1118 were added while stirring. The system was heated to 82°C and refluxed for 5 minutes.

[0057] 2. Mix 44 parts of acrylic acid monomer (1.32 parts of methacrylic acid, 2.2 parts of butyl acrylate, 11 parts of methyl methacrylate, 29.48 parts of isooctyl acrylate) and 0.05 parts of BPO evenly. 2 After deoxygenation for 30 minutes, add it into the reactor at one time;

[0058] 3. Maintain the system at 82°C, continue the reaction for 4 hours, then cool down to 72°C;

[0059] 4. Mix the remaining 176 parts of acrylic acid monomer, 0.11 parts of AIBN, and 176 parts of toluene evenly. 2 After deoxygenation for 30 minutes, add dropwise to the reactor for 1.5 hours;

[0060] 5. Maintain the system at 72°C, react for 2 hours, then add 0.055 parts of AIBN every 1 hour for a total of 3 times;

[0061] 6. After the last addition of AIBN, react for 1.5 h, add the remaining toluene to cool down and cool to room temperature.

[0062] Preparation of Foam Tape

[0063] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0064]

[0065] Prepare the foam tape as follows:

[0066] 1. Add materials into the container in the following order: dissolve the solvent and tackifying resin in a ratio of 1:1 at 500 rpm until no particles remain; then add the foam masterbatch and stir at a speed of 1200 rpm for 20 minutes; add the foaming agent and curing agent and mix them evenly at a speed of 500 rpm and adjust the solid content to 25±1% with the solvent to prepare the coating solution;

[0067] 2. Vacuum degassing the coating liquid prepared above, filtering it through a three-core 10um filter element, and then evenly coating it on the release film;

[0068] 3. The coated release film is passed through a coating machine with 7 ovens, continuously heated, dried and foamed to form a high-rigidity impact-resistant foam tape with a thickness of 200um. The first section has a temperature of 60-70°C, the second section has a temperature of 70-85°C, the third section has a temperature of 85-110°C, the fourth section has a temperature of 110-155°C, the fifth section has a temperature of 110-155°C, the sixth section has a temperature of 130-110°C, and the seventh section has a temperature of 110-90°C.

[0069] Example 2

[0070] Preparation of Foam Masterbatch

[0071] According to the mass fraction, the composition of the foam masterbatch is as follows: the theoretical TG after the copolymerization of the acrylic ester monomer is -38.78°C;

[0072]

[0073] Prepare the foam masterbatch as follows:

[0074] 1. N 2 In the atmosphere, 200 parts of toluene were placed in a 50L reactor, and 50 parts of SBS D1116 were added while stirring. The system was heated to 82°C and refluxed for 5 minutes.

[0075] 2. Mix 44 parts of acrylic acid monomer (1.32 parts of methacrylic acid, 2.2 parts of butyl acrylate, 11 parts of methyl methacrylate, 29.48 parts of isooctyl acrylate) and 0.05 parts of BPO evenly. 2 After deoxygenation for 30 minutes, add it into the reactor at one time;

[0076] 3. Maintain the system at 82°C, continue the reaction for 4 hours, then cool down to 72°C;

[0077] 4. Mix the remaining 176 parts of acrylic acid monomer, 0.11 parts of AIBN, and 176 parts of toluene evenly. 2 After deoxygenation for 30 minutes, add dropwise to the reactor for 1.5 hours;

[0078] 5. Maintain the system at 72°C, react for 2 hours, then add 0.055 parts of AIBN every 1 hour for a total of 3 times;

[0079] 6. After the last addition of AIBN, react for 1.5 h, add the remaining toluene to cool down and cool to room temperature.

[0080] Preparation of Foam Tape

[0081] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0082]

[0083]

[0084] Prepare the foam tape as follows:

[0085] 1. Add materials into the container in the following order: dissolve the solvent and tackifying resin in a ratio of 1:1 at 500 rpm until no particles remain; then add the foam masterbatch and stir at a speed of 1200 rpm for 20 minutes; add the foaming agent and curing agent and mix them evenly at a speed of 500 rpm and adjust the solid content to 25±1% with the solvent to prepare the coating solution;

[0086] 2. Vacuum degassing the coating liquid prepared above, filtering it through a three-core 10um filter element, and then evenly coating it on the release film;

[0087] 3. The coated release film is passed through a coating machine with 7 ovens, continuously heated, dried and foamed to form a high-rigidity impact-resistant foam tape with a thickness of 200um. The first section has a temperature of 60-70°C, the second section has a temperature of 70-85°C, the third section has a temperature of 85-110°C, the fourth section has a temperature of 110-155°C, the fifth section has a temperature of 110-155°C, the sixth section has a temperature of 130-110°C, and the seventh section has a temperature of 110-90°C.

[0088] Example 3

[0089] Preparation of Foam Masterbatch

[0090] According to the mass fraction, the composition of the foam masterbatch is as follows: the theoretical TG after the copolymerization of the acrylic ester monomer is -38.78°C;

[0091]

[0092] Prepare the foam masterbatch as follows:

[0093] 1. N 2 In the atmosphere, 200 parts of toluene were placed in a 50L reactor, and 50 parts of VECTOR4213 were added while stirring. The system was heated to 82°C and refluxed for 5 minutes.

[0094] 2. Mix 44 parts of acrylic acid monomer (1.32 parts of methacrylic acid, 2.2 parts of butyl acrylate, 11 parts of methyl methacrylate, 29.48 parts of isooctyl acrylate) and 0.05 parts of BPO evenly. 2 After deoxygenation for 30 minutes, add it into the reactor at one time;

[0095] 3. Maintain the system at 82°C, continue the reaction for 4 hours, then cool down to 72°C;

[0096] 4. Mix the remaining 176 parts of acrylic acid monomer, 0.11 parts of AIBN, and 176 parts of toluene evenly. 2 After deoxygenation for 30 minutes, add dropwise to the reactor for 1.5 hours;

[0097] 5. Maintain the system at 72°C, react for 2 hours, then add 0.055 parts of AIBN every 1 hour for a total of 3 times;

[0098] 6. After the last addition of AIBN, react for 1.5 h, add the remaining toluene to cool down and cool to room temperature.

[0099] Preparation of Foam Tape

[0100] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0101]

[0102] Prepare the foam tape as follows:

[0103] 1. Add materials into the container in the following order: dissolve the solvent and tackifying resin in a ratio of 1:1 at 500 rpm until no particles remain; then add the foam masterbatch and stir at a speed of 1200 rpm for 20 minutes; add the foaming agent and curing agent and mix them evenly at a speed of 500 rpm and adjust the solid content to 25±1% with the solvent to prepare the coating solution;

[0104] 2. Vacuum degassing the coating liquid prepared above, filtering it through a three-core 10um filter element, and then evenly coating it on the release film;

[0105] 3. The coated release film is passed through a coating machine with 7 ovens, continuously heated, dried and foamed to form a high-rigidity impact-resistant foam tape with a thickness of 200um. The first section has a temperature of 60-70°C, the second section has a temperature of 70-85°C, the third section has a temperature of 85-110°C, the fourth section has a temperature of 110-155°C, the fifth section has a temperature of 110-155°C, the sixth section has a temperature of 130-110°C, and the seventh section has a temperature of 110-90°C.

[0106] Example 4

[0107] Preparation of Foam Masterbatch

[0108] According to the mass fraction, the composition of the foam masterbatch is as follows: the theoretical TG after the copolymerization of the acrylic ester monomer is -38.78°C;

[0109]

[0110] Prepare the foam masterbatch as follows:

[0111] 1. N 2In the atmosphere, 200 parts of toluene were placed in a 50L reactor, and 50 parts of SBS D1118 were added while stirring. The system was heated to 82°C and refluxed for 5 minutes.

[0112] 2. Mix 22 parts of acrylic acid monomer (0.66 parts of methacrylic acid, 1.1 parts of butyl acrylate, 5.5 parts of methyl methacrylate, 14.74 parts of isooctyl acrylate) and 0.05 parts of BPO. 2 After deoxygenation for 30 minutes, add it into the reactor at one time;

[0113] 3. Maintain the system at 82°C, continue the reaction for 4 hours, then cool down to 72°C;

[0114] 4. Mix the remaining 88 parts of acrylic acid monomer, 0.055 parts of AIBN, and 88 parts of toluene evenly. 2 After deoxygenation for 30 minutes, add dropwise to the reactor for 1.5 hours;

[0115] 5. Maintain the system at 72°C, react for 2 hours, then add 0.0275 parts of AIBN every 1 hour for a total of 3 times;

[0116] 6. After the last addition of AIBN, react for 1.5 h, add the remaining toluene to cool down and cool to room temperature.

[0117] Preparation of Foam Tape

[0118] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0119]

[0120] Prepare the foam tape as follows:

[0121] 1. Add materials into the container in the following order: dissolve the solvent and tackifying resin in a ratio of 1:1 at 500 rpm until no particles remain; then add the foam masterbatch and stir at a speed of 1200 rpm for 20 minutes; add the foaming agent and curing agent and mix them evenly at a speed of 500 rpm and adjust the solid content to 25±1% with the solvent to prepare the coating solution;

[0122] 2. Vacuum degassing the coating liquid prepared above, filtering it through a three-core 10um filter element, and then evenly coating it on the release film;

[0123] 3. The coated release film is passed through a coating machine with 7 ovens, continuously heated, dried and foamed to form a high-rigidity impact-resistant foam tape with a thickness of 200um. The first section has a temperature of 60-70°C, the second section has a temperature of 70-85°C, the third section has a temperature of 85-110°C, the fourth section has a temperature of 110-155°C, the fifth section has a temperature of 110-155°C, the sixth section has a temperature of 130-110°C, and the seventh section has a temperature of 110-90°C.

[0124] Example 5

[0125] Preparation of Foam Masterbatch

[0126] According to the mass fraction, the composition of the foam masterbatch is as follows: the theoretical TG after the copolymerization of the acrylic ester monomer is -19.54°C;

[0127]

[0128]

[0129] Prepare the foam masterbatch as follows:

[0130] 1. N 2 In the atmosphere, 200 parts of toluene were placed in a 50L reactor, and 50 parts of SBS D1118 were added while stirring. The system was heated to 82°C and refluxed for 5 minutes.

[0131] 2. Mix 44 parts of acrylic acid monomer (1.32 parts of methacrylic acid, 17.6 parts of methyl methacrylate, 25.08 parts of isooctyl acrylate) and 0.05 parts of BPO evenly. 2 After deoxygenation for 30 minutes, add it into the reactor at one time;

[0132] 3. Maintain the system at 82°C, continue the reaction for 4 hours, then cool down to 72°C;

[0133] 4. Mix the remaining 176 parts of acrylic acid monomer, 0.11 parts of AIBN, and 176 parts of toluene evenly. 2 After deoxygenation for 30 minutes, add dropwise to the reactor for 1.5 hours;

[0134] 5. Maintain the system at 72°C, react for 2 hours, then add 0.055 parts of AIBN every 1 hour for a total of 3 times;

[0135] 6. After the last addition of AIBN, react for 1.5 h, add the remaining toluene to cool down and cool to room temperature.

[0136] Preparation of Foam Tape

[0137] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0138]

[0139] Prepare the foam tape as follows:

[0140] 1. Add materials into the container in the following order: dissolve the solvent and tackifying resin in a ratio of 1:1 at 500 rpm until no particles remain; then add the foam masterbatch and stir at a speed of 1200 rpm for 20 minutes; add the foaming agent and curing agent and mix them evenly at a speed of 500 rpm and adjust the solid content to 25±1% with the solvent to prepare the coating solution;

[0141] 2. Vacuum degassing the coating liquid prepared above, filtering it through a three-core 10um filter element, and then evenly coating it on the release film;

[0142] 3. The coated release film is passed through a coating machine with 7 ovens, continuously heated, dried and foamed to form a high-rigidity impact-resistant foam tape with a thickness of 200um. The first section has a temperature of 60-70°C, the second section has a temperature of 70-85°C, the third section has a temperature of 85-110°C, the fourth section has a temperature of 110-155°C, the fifth section has a temperature of 110-155°C, the sixth section has a temperature of 130-110°C, and the seventh section has a temperature of 110-90°C.

[0143] Comparative Example 1

[0144] Preparation of Foam Masterbatch

[0145] The foam masterbatch was prepared by the same method as in Example 1, except that the mass ratio of the acrylate monomer to the block copolymer in the composition of the foam masterbatch was B / S=1, which was not within the range of 1.5 to 5. Specifically, in terms of mass parts, the composition of the foam masterbatch was as follows:

[0146]

[0147] Foam tape preparation

[0148] The foam tape was prepared by the same method as in Example 1, and the tape composition was as follows:

[0149] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0150]

[0151]

[0152] Comparative Example 2

[0153] Preparation of Foam Masterbatch

[0154] The foam masterbatch was prepared by the same method as in Example 1, except that the mass ratio of the acrylic ester monomer to the block copolymer in the composition of the foam masterbatch was B / S=6, which was not within the range of 1.5 to 5. Specifically, in terms of mass parts, the composition of the foam masterbatch was as follows:

[0155]

[0156] Preparation of Foam Tape

[0157] The foam tape was prepared by the same method as in Example 1, and the tape composition was as follows:

[0158] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0159]

[0160] Comparative Example 3

[0161] Preparation of Foam Masterbatch

[0162] The foam masterbatch was prepared by the same method as in Example 1, except that the theoretical TG of the acrylate monomer after copolymerization in the composition of the foam masterbatch was 0.69° C., which was not within the range of -40 to -20° C. Specifically, in terms of parts by mass, the composition of the foam masterbatch was as follows:

[0163]

[0164] Preparation of Foam Tape

[0165] The foam tape was prepared by the same method as in Example 1, and the tape composition was as follows:

[0166] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0167]

[0168] Comparative Example 4

[0169] Preparation of Foam Masterbatch

[0170] The foam masterbatch was prepared by the same method as in Example 1, except that the theoretical TG of the acrylate monomer after copolymerization in the composition of the foam masterbatch was -50.66°C, which was not within the range of -40 to -20°C. Specifically, in terms of parts by mass, the composition of the foam masterbatch was as follows:

[0171]

[0172]

[0173] Preparation of Foam Tape

[0174] The foam tape was prepared by the same method as in Example 1, and the tape composition was as follows:

[0175] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0176]

[0177] Comparative Example 5

[0178] Preparation of Foam Masterbatch

[0179] The foam masterbatch was prepared by the same method as in Example 1, except that the styrene content of the block copolymer SIS3421 used was 14%. Specifically, in terms of mass parts, the composition of the foam masterbatch was as follows:

[0180]

[0181]

[0182] Preparation of Foam Tape

[0183] The foam tape was prepared by the same method as in Example 1. The composition of the foam tape coating liquid was as follows in parts by mass:

[0184]

[0185] Comparative Example 6

[0186] The difference from Example 1 is that the acrylic acid graft modified block copolymer and the acrylic acid copolymer are respectively carried out in different reactors, and then the two are mixed evenly by blending, and then the tackifying resin and other additives are added to prepare the foam tape coating liquid.

[0187] Preparation of acrylic acid graft modified block copolymer

[0188]

[0189] 1. N 2 In the atmosphere, 200 parts of toluene were placed in a 50L reactor, and 50 parts of SBSD1118 were added while stirring. The system was heated to 82°C and refluxed for 5 minutes.

[0190] 2. Mix 44 parts of acrylic acid monomer (1.32 parts of methacrylic acid, 2.2 parts of butyl acrylate, 11 parts of methyl methacrylate, 29.48 parts of isooctyl acrylate) and 0.05 parts of BPO evenly. 2 After deoxygenation for 30 minutes, add it into the reactor at one time;

[0191] 3. Maintain the system at 82°C, continue the reaction for 4 hours, then cool down to obtain the acrylic acid grafted modified block copolymer.

[0192] Preparation of acrylic adhesive

[0193]

[0194] 1. In a N2 atmosphere, mix 176 parts of acrylic acid monomer and 176 parts of toluene evenly. 2 After deoxygenation for 30 minutes, add it into the reactor, control the system temperature to 72°C, and reflux for 5 minutes;

[0195] 2. Add 0.11 parts of AIBN and observe the system. When small bubbles appear, record the time t==0.

[0196] 3. Maintain the system at 72°C, react for 2 hours, then add 0.055 parts of AIBN every 1 hour for a total of 3 times;

[0197] 4. After the last addition of AIBN, react for 1.5 h, add the remaining toluene to cool down and cool to room temperature.

[0198] Preparation of Foam Tape

[0199] According to parts by mass, the composition of the foam tape coating liquid is as follows:

[0200]

[0201] Prepare the foam tape as follows:

[0202] 1. Add materials into the container in order: the solvent and the tackifying resin are fully dissolved at a ratio of 1:1 at 500 rpm until no particles remain; then add the acrylate graft-modified block copolymer, and stir the acrylate adhesive at a high speed of 1200 rpm for 20 minutes; add the foaming agent and the curing agent, mix them evenly at a speed of 500 rpm, and adjust the solid content to 25±1% with the solvent to prepare the coating solution;

[0203] 2. Vacuum degassing the coating liquid prepared above, filtering it through a three-core 10um filter element, and then evenly coating it on the release film;

[0204] 3. The coated release film is passed through a coating machine with 7 ovens, continuously heated, dried and foamed to form a high-rigidity impact-resistant foam tape with a thickness of 200um. The first section has a temperature of 60-70°C, the second section has a temperature of 70-85°C, the third section has a temperature of 85-110°C, the fourth section has a temperature of 110-155°C, the fifth section has a temperature of 110-155°C, the sixth section has a temperature of 130-110°C, and the seventh section has a temperature of 110-90°C.

[0205] The performance test comparison of the foam tapes prepared in Examples 1-5 and Comparative Examples 1-6 is shown in the following table:

[0206]

[0207] Test project description:

[0208] 1. 180° peeling force test on SUS steel plate

[0209] The test was carried out in accordance with the standard “Test method for peel strength of adhesive tape” (GB / T2792-2014).

[0210] 2. Stiffness test

[0211] (1) Prepare two 6061-T6 aluminum plates with a size of 2mm*12mm*200mm and wipe them clean with isopropyl alcohol;

[0212] (2) Stick the foam tape on one of the aluminum plates and cover it with another aluminum plate. Press it back and forth three times with a 2KG roller. Leave it at room temperature for 20 minutes before testing. Figure 1 As shown;

[0213] (3) Press Figure 1 As shown, the spline is placed on the fixture, the pressing speed is set to 0.05 mm / s, and the vertical displacement w1 of the spline bending downward at 6.66 N and the vertical displacement w2 of the spline bending downward at 20 N are recorded;

[0214] (4) Calculated stiffness = 13.34 / (w2-w1).

[0215] 3. Impact test

[0216] (1) Cut the foam tape into a U-shaped sample with an outer side length of 24.5 mm and an inner side length of 20.5 mm;

[0217] (2) Figure 2 As shown, the U-shaped sample was attached to a U-shaped stainless steel frame (outer side length 40 mm, inner side length 20 mm), and then a square stainless steel cover plate (side length 24.5 mm) was attached to the other side of the U-shaped sample. A force of 62 N was applied for 10 seconds and the sample was placed at room temperature for 48 hours.

[0218] (3) Use a total impact energy of 30.4 J and a height of 205 mm for penetrating impact, and record the total energy absorbed by the damage.

[0219] Conclusion: The method of preparing foam masterbatch by first grafting block copolymer with acrylic acid and then copolymerizing with acrylic acid in the same reactor can avoid phase separation during the standing process of the coating liquid. At the same time, designing and specifying the theoretical TG and content of acrylic ester monomers can ensure the adhesion, impact resistance and stiffness of the foam tape to meet application requirements.

[0220] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A high-rigidity impact-resistant foam masterbatch, characterized in that: It includes a block copolymer, an acrylate monomer, a solvent, and an initiator; the mass fraction of the block copolymer is set to S, the mass fraction of the acrylate monomer is set to B, then 1.5≤B / S≤5, and the theoretical TG of the acrylate monomer after copolymerization alone is -40 to -20°C.

2. The high-rigidity impact-resistant foam masterbatch according to claim 1, characterized in that: The solid content of the high-rigidity impact-resistant foam masterbatch is 20-50%, the solvent is set to R parts by mass, and the initiator is set to Y parts by mass; then: 20%≤(S+B+Y) / (S+B+Y+R)≤50%.

3. The high-rigidity impact-resistant foam masterbatch according to claim 1, characterized in that: The block copolymer has a styrene content of >20%.

4. The high-rigidity impact-resistant foam masterbatch according to claim 1, characterized in that: The foam masterbatch is prepared by firstly carrying out acrylate grafting modification of block copolymer and then carrying out acrylate copolymerization in the same reaction container.

5. The high-rigidity impact-resistant foam masterbatch according to claim 1, characterized in that: The block copolymer is one or more of SBS, SIS, and SEBS; The acrylic acid ester monomer is one or more of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, n-butyl acrylate, isobutyl acrylate, isooctyl acrylate, isobornyl acrylate, isobornyl methacrylate, cyclohexyl methacrylate, hydroxybutyl acrylate, ureidomethyl acrylate, ethyl diethylene glycol acrylate, and tert-butyl acrylate; The initiator is a peroxide and / or an azo compound; The solubility parameter of the solvent 1 is 7.6-9.

8.

6. A method for preparing a high-rigidity impact-resistant foam masterbatch, comprising the following steps: In a N2 atmosphere, add solvent 1 and all block copolymers into the reactor in sequence to make the solid content of the block copolymer 10-30%, and heat and reflux for 5-10 minutes; 0.2B parts by mass of acrylic acid monomer and 0.0001S to 0.01S parts by mass of initiator were mixed evenly, and after deoxygenation with N2, they were added into the reactor and the reaction was continued for 3-5 hours; 0.8B parts by mass of acrylic acid monomer, 0.00008B to 0.008B parts by mass of initiator, and 0.8B parts by mass of solvent were mixed evenly, and after deoxygenation with N2, the mixture was added dropwise to the reactor over a period of 1-1.5h, and the reaction was continued for 1-2h; Every 1 hour, add 0.00004B to 0.004B parts by mass of initiator until all the remaining initiator is added. After reacting for 1-2 hours, add the remaining solvent and cool to room temperature to obtain a high-rigidity impact-resistant foam masterbatch.

7. A high-rigidity impact-resistant foam tape, characterized in that: The composition comprises, by mass, 100 parts of the foam masterbatch according to any one of claims 1 to 6, 0.1 to 5 parts of a foaming agent, 0 to 300 parts of a tackifying resin, 0.1 to 5 parts of a curing agent, and 0 to 400 parts of a solvent 2; Except for solvent 2, the remaining components are calculated according to the solid components.

8. The high-rigidity impact-resistant foam tape according to claim 7, characterized in that: The curing agent is one or more of an isocyanate curing agent, an epoxy curing agent, and a metal salt curing agent; The second solvent is one or more of toluene, ethyl acetate, heptane, butyl acetate, and butanone; The foaming agent is one or more of foaming microspheres, hydrocarbon foaming agents, and carbon dioxide foaming agents; The tackifying resin is one or two of terpene resins, rosin resins, esterified rosin resins and petroleum resins.

9. The method for preparing the high-rigidity impact-resistant foam tape according to any one of claims 7 to 8, comprising the following steps: S1: Add materials into the container in the following order: Solvent 2 and tackifying resin are fully dissolved until no particles remain; then add foam masterbatch and stir at high speed for 10-30 minutes; add foaming agent and curing agent, mix well and adjust the solid content to 20-35% with solvent 2 to prepare coating solution; S2: The coating liquid prepared above is filtered and degassed, and then evenly coated on a release film. After drying, foaming, and laminating, a high-rigidity impact-resistant foam tape is obtained.

10. An application of a high-rigidity impact-resistant foam tape, characterized in that: The high-rigidity impact-resistant foam tape described in any one of claims 7 to 8 or the high-rigidity impact-resistant foam tape obtained by the preparation method according to claim 9 is applied to modern display and smart devices.

Citation Information

Patent Citations

  • Impact resistant pressure sensitive adhesive

    CN117730128A

  • (Meth)acrylate-based toughening adhesive

    KR1020247026664

  • Tightly-sticking type substrate-free double-sided adhesive tape and its preparation method

    CN109852268A

  • SIS elastomer grafted compound A and composition thereof as well as preparation method of polyethylene foam double-sided tape

    CN109913144A

  • Novel acrylic-modified rubber foam-use resin and preparation method thereof

    CN110396160A